METAVERSE MARKETING: CONCEPTUAL FOUNDATIONS AND A RESEARCH AGENDA FOR BRAND PRESENCE, COMMUNITY, AND COMMERCE - Subekti; Lukmanul Hakim; Tibrani (RADJA PUBLIKA, 2026)
This article examines the conceptual foundations of metaverse marketing and proposes a research agenda centered on three core dimensions: brand presence, community, and commerce. As immersive technologies such as virtual reality, augmented reality, blockchain, and artificial intelligence converge, the metaverse is emerging as a transformative environment for marketing practice. Drawing on a narrative literature review across marketing, technology, and consumer behavior, this study highlights the shift from traditional digital marketing toward interactive, experiential, and participatory engagement. The findings emphasize that effective brand presence in the metaverse requires immersive experiences and virtual storytelling, while community plays a critical role in fostering social interaction, co-creation, and brand advocacy. Commerce introduces new opportunities for value creation through virtual goods, digital assets, and decentralized transactions enabled by blockchain technologies. The article proposes a conceptual framework that integrates these three pillars and identifies key interaction mechanisms, including co-creation, engagement, and transactions, which drive outcomes such as brand equity, loyalty, and economic value. Additionally, moderating factors such as technology adoption, consumer motivations, and platform trust are discussed. The study contributes by offering a holistic framework and outlining future research directions for understanding and leveraging metaverse marketing.